Walking gait asymmetries 6 months following anterior cruciate ligament reconstruction predict 12‐month patient‐reported outcomes. Issue 11 (13th July 2018) - Pietrosimone, Brian; Blackburn, J. Troy; Padua, Darin A.; Pfeiffer, Steven J.; Davis, Hope C.; Luc‐Harkey, Brittney A.; Harkey, Matthew S.; Stanley Pietrosimone, Laura; Frank, Barnett S.; Creighton, Robert Alexander; Kamath, Ganesh M.; Spang, Jeffery T.
ABSTRACT: The study sought to determine the association between gait biomechanics (vertical ground reaction force [vGRF], vGRF loading rate [vGRF‐LR]) collected 6 months following anterior cruciate ligament reconstruction (ACLR) with patient‐reported outcomes at 12 months following ACLR. Walking gait biomechanics and all subsections of the Knee Injury and Osteoarthritis Outcomes Score (KOOS) were collected at 6 and 12 months following ACLR, respectively, in 25 individuals with a unilateral ACLR. Peak vGRF and peak instantaneous vGRF‐LR were extracted from the first 50% of the stance phase. Limb symmetry indices (LSI) were used to normalize outcomes in the ACLR limb to that of the uninjured limb (ACLR/uninjured). Linear regression analyses were used to determine associations between biomechanical outcomes and KOOS while accounting for walking speed. Receiver operator characteristic curves were used to determine the accuracy of 6‐month biomechanical outcomes for identifying individuals with acceptable patient‐reported outcomes, using previously defined KOOS cut‐off scores, 12 months post‐ACLR. Individuals with lower peak vGRF LSI 6 months post‐ACLR demonstrated worse patient‐reported outcomes (KOOS Pain, Activities of Daily life, Sport and Recreation, Quality of Life) at the 12‐month exam. A peak vGRF LSI ≥0.99 6 months following ACLR associated with 13.33× higher odds of reporting acceptable patient‐reported outcomes 12 months post‐ACLR. Lesser peak vGRF LSI during walking at 6‐months post‐ACLR may be a critical indicator of worse future patient‐reported outcomes. Clinical significance achieving early symmetrical lower extremity loading and minimizing under‐loading of the ACLR limb during walking may be a potential therapeutic target for improving patient‐reported outcomes post‐ACLR. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:2932–2940, 2018.